TRANSFORMING SPEAKING SKILLS WITH STORYTELLING: A STUDY AT MTS MUHAMMADIYAH AL-HAQ PALU - Annisa Khaerarani Adam; Sriati Usman; Desrin Lebagi; Darmawan (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Speaking skills are one aspect that needs to be develop in context of language learning. However, there are still many students who have difficulty in mastering this skill, because of the lack of knowledge of vocabulary and grammar, cause a lack of confidence in students when they want to speak English. This study investigates the effectiveness of the storytelling technique in enhancing the speaking skills of eighth-grade students at MTs Muhammadiyah Al-Haq Palu. Addressing the urgent need for engaging and student-centered strategies to improve oral proficiency, this research offers empirical evidence on the value of storytelling in English language learning. A quasi-experimental method was employed using pre-test and post-test procedures in both experimental and control groups. Thirty students were selected through convenience sampling, with fifteen assigned to each group. The experimental group received six sessions of storytelling-based instruction, while the control group learned through conventional methods. Findings reveal a substantial improvement in the experimental group, which achieved a post-test mean score of 69.33, compared to 44.67 in the control group. The novelty of this study lies in demonstrating storytelling as an effective instructional technique within the Indonesian Islamic junior high school context. The results contribute to pedagogical practices by supporting storytelling as a practical approach to improving students’ speaking skills.